Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae) - Semenyuk, Irina; Golovatch, Sergei I.; Wesener, Thomas (Zootaxa, 2018)
Four new species of giant pill-millipedes (Sphaerotheriida) are described from southern Vietnam: Sphaerobelum cattiense sp. nov., Sphaerobelum konkakinhense sp. nov., Zephronia konkakinhensis sp. nov. and Zephronia montis sp. nov. An updated generic diagnosis of Sphaerobelum Verhoeff, 1924 and a key to its species are provided.